Aerobic exercise training during pregnancy increases antioxidant status in nulliparous women: secondary analysis of a controlled clinical trial (2013)
Several hypotheses invoke oxidative stress as a cellular process contributing to endothelial dysfunction in preeclampsia and a plausible convergence point for interaction of the fetoplacental unit and maternal predisposing factors involved in this disorder.1 A recent summary from the National Heart, Lung, and Blood Institute Working Group on Research on Hypertension during Pregnancy2 recommended clinical trials to assess whether exercise training could prevent preeclampsia by reducing oxidative stress and enhancing antioxidant defense systems3,4; it is not known if exercise produces this effect during pregnancy. Therefore, the research question for this study was: does a 12-week supervised aerobic exercise program enhance antioxidant status in pregnant women, which reduces oxidative stress and in turn the incidence of preeclampsia?